Enforcing obligations erga omnes in international law - Tams, Christian J. (Cambridge : Cambridge University Press, 2010)
The concept of obligations erga omnes - obligations to the international community as a whole - has fascinated international lawyers for decades, yet its precise implications remain unclear. This book assesses how this concept affects the enforcement of international law.
Originally published: 2005.
Includes bibliographical references (pages 339-377) and index.
Keywords: International obligations; International law -- Moral and ethical aspects; Customary law, International; Customary law, International; International law -- Moral and ethical aspects; International obligations